2012
DOI: 10.2119/molmed.2011.00404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nuclear Factor κB Inhibition on Serotype 9 Adeno-Associated Viral (AAV9) Minidystrophin Gene Transfer to the mdx Mouse

Abstract: Gene therapy studies for Duchenne muscular dystrophy (DMD) have focused on viral vector-mediated gene transfer to provide therapeutic protein expression or treatment with drugs to limit dystrophic changes in muscle. The pathological activation of the nuclear factor (NF)-κB signaling pathway has emerged as an important cause of dystrophic muscle changes in muscular dystrophy. Furthermore, activation of NF-κB may inhibit gene transfer by promoting inflammation in response to the transgene or vector. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is also noteworthy that AAV9 constructs, despite their well-established tropism for cardiac myocytes, 54, 55 also transduce skeletal muscles, including the diaphragm, and to a lesser extent the liver. 56, 57 Consequently, the survival benefit observed in the Lmna −/− mice upon administration of AAV9- Foxo shRNA might be due to the effects of suppression of FOXO TF in other organs, such as the striated respiratory muscles, prevention of muscle atrophy, and the resultant improvement in respiratory efficiency, as shown in other models. 58, 59…”
Section: Discussionmentioning
confidence: 97%
“…It is also noteworthy that AAV9 constructs, despite their well-established tropism for cardiac myocytes, 54, 55 also transduce skeletal muscles, including the diaphragm, and to a lesser extent the liver. 56, 57 Consequently, the survival benefit observed in the Lmna −/− mice upon administration of AAV9- Foxo shRNA might be due to the effects of suppression of FOXO TF in other organs, such as the striated respiratory muscles, prevention of muscle atrophy, and the resultant improvement in respiratory efficiency, as shown in other models. 58, 59…”
Section: Discussionmentioning
confidence: 97%
“…While there is promising evidence to help attenuate DMD disease pathology, most of these studies have been limited to DMD animal models and only few have progressed into clinical trials in DMD patients (recently reviewed in Verhaart et al [ 89 ]). Interestingly, it has been shown that treatment with NFκB inhibitors allowed for a higher mini-dystrophin expression induced via AAV treatment in mdx mice than without treatment, suggesting that it helps the transduction of the mini-dystrophin into the muscle [ 90 ]. This supports the idea of a combinatorial therapy for DMD that will involve anti-inflammatory/antioxidant treatment with a gene therapy to restore muscle stability and function.…”
Section: Discussionmentioning
confidence: 99%
“…Short hairpin RNA carrier AAV9 has been successfully developed to target the major subunit of NF-›B (NF-›B/p65) and ameliorate muscle pathologic phenotype in mdx mice [160]. Finally, AAV9 mini-dystrophin gene delivery combined to the addition of octalysine (8K)-NF-›B essential modulator (NEMO)-Binding Domain (8K-NBD) peptide promoted a higher mini-dystrophin expression in skeletal muscle compared to AAV9 alone [161].…”
Section: Adeno-associated Virus (Aav)mentioning
confidence: 99%